Digital Globalization in the International Development of Strategic Alliances - Mikhno, Inesa; Koval, Viktor; Sedikova, Iryna; Kotlubai, Viacheslav (Dr. Viktor Koval, 2022)
Abstract. Over the past century, the rate of globalization has substantially grown due to the increasing impact of transnational companies, development of digital communications systems, integration of new technologies and the increasing need for rapid response to changes by transforming life orientations of society. Establishment of strategic alliances and enlargement of international companies are becoming more relevant in the digital services and informational support sector because of the constant development of technologies and the enhancement of legislation in many countries regarding authors' rights, patenting and intellectual property, which encourages the search for new possibilities of reducing corporate expenses and expanding sales markets and influence. Aim and tasks. The article is aimed at examining key globalization processes in the development of strategic alliances of transnational companies in the period of economy digitalization and providing recommendations for improving ecological and economic situations caused by globalization in developing countries. Results. The article analyzes key risks caused by globalization processes, Ukraine’s current situation and future trends. It analyzes Ukraine’s major transnational companies and their operating strategies, develops an activity scheme of donor countries of transnational corporations and recipient countries that most frequently serve as a financial or resource potential for the company. One has advanced an assessment model of the globalization level in the country, developed the table of globalization effects. Using KOF Globalisation Index, one has made a forecast for the future of Ukraine and other countries, provided recommendations for improving its calculation by putting an index of ecological impact of international companies on the situation in the country and the ecosystem before and after company’s entrance to the national market.     Conclusions. Digital globalization processes increase the impact on international markets and establish a separate market of international digital services. Therefore, the establishment of strategic alliances based on digitalization and intelligent technologies enhances the efficiency of activities of transnational companies but requires further advancement of institutional support in the development of regulated rules of conduct on the information market. Following the analysis results, one has found out that the core problem of international companies operating in the territory of developing countries is the irrational use of natural resources. One has proven that, taking into account the level of globalization, it is viable to estimate the ecological impact of international companies on the ecosystem state in the given country, examine changes caused by globalization processes in natural systems as a result of social and political globalization changes in order to protect the economy and natural resources from the irrational use.